Software defined telecommunication networks - Slyne, Frank (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2016)
The paradigm of Software Defined Networking can have significant beneficial impacts on the provision of traditional Telecommunications services, but there is a possibility that networks may be oversimplified by removing hidden but important components. We evaluate the impacts of applying Software Defined Network principles to constraints that have been built in, over time, into traditional Telecommunications networks. We adopt a two stranded approach. The first strand evaluates the interaction between a state of the art control plane and a converged network (Long reach PON) architecture, through the application of a number of typical but important scenarios. The first strand gathers data from physical testbeds that were constructed specifically for the experiments. The second strand evaluates innovation in the Layer 2 data plane, made possible by the application of SDN principles, again through the application of a number of typical scenarios. The second strand relies on a mix of simulation, predominantly, and physical experimentation. To evaluate the effect of SDN on the converged network architecture, we construct a number of testbeds involving substantial state-of-the-art components that create an end-to-end telecommunications network. A number of testbeds are used that facilitate different technological aspects of the network, as well as the skillsets of the centres involved. The complexity of the testbeds and their integrations developed over time to reflect the availability of components. The experiments that were execute involved the performance and capability in the provisioning of high capacity bandwidth, as well as the speed of failover of network paths across a wide area, that is both on the scale of a National Network as well as a Continental Network. The experiments are executed a number of times, to understand any underlying artefacts in the interaction between the control plane and the data plane. The Protection use case exemplifies how path integrity in the Core and TDM-DWDM LRPON based Access Metro network of a Telecommunications network can be assured through logical protection. The protection experiment demonstrated a dual-homed LR-PON protection mechanism where backup OLTs are shared among PONs in an N:1 scheme and the service restoration is provided over an end-to-end Software Defined Network. The DWA use case exemplifies how capacity constraints in one PON channel may be overcome by re-allocating dynamically one or more end user ONUs to a different channel in order to assure quality of service. This could also be used for the opportunistic provision of high bandwidth services (on-demand video and big data transfers), to specific PON users on a dynamic basic. To evaluate the Data Plane architecture aspects, we propose and model a design for a flat Telecommunications architecture that is theoretically more scalable and efficient when compared to traditional architectures. This architecture is called FLATLANd (short for Flat Layer Two Telecommunications Network). The proposed structure provides a number of benefits. Firstly, the architecture is strictly flat and conducts all traffic at a single layer – that is layer 2 without the use of tunnelling, VPN nor labels. Secondly, the architecture is inherently Open Access in that no one network nor service provider dominates over the others, as is the case in traditional wholesale and retail models for broadband access networks. Thirdly, the addressing is extremely scalable and granular, accommodating many terminating nodes as well as service types. Rather than preserving legacy devices such as B-RAS in their physical or virtual form, we re-architect the entire network from first principles. We target in particular next generation optical broadband networks, and take into consideration the convergence of access and metro networks, using the Long-Reach PON (LR-PON) architecture.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin